REVERSAL BURDEN OF PROOF IN PROCESS OF PROVING MONEY LAUNDERING CASES IN INDONESIA - Febriansyah, Artha; Zulfa, Eva Achjani; Yusuf, Muhammad; Banjarani, Desia (UI Scholars Hub, 2023)
The implementation of reversal burden of proof in money laundering cases still faces obstacles that cause suboptimal and ineffective in legal enforcement. It raises a debate regarding the existence of reversal burden of proof in the proving system, particularly the proof of the crime of money laundering. Based on this background, the problems in this research are related to the regulation and implementation of reversal burden of proof in the process of proving money laundering cases and the steps that can be taken in optimizing the application of reversal burden of proof in the process of proving money laundering cases. The method used in this research is normative research which is supported by empirical data. The results of the study shows that the regulation regarding the reversal burden of proof in the criminal justice system in Indonesia can be found in several Indonesian legal provisions. Regarding the implementation of the reversal burden of proof, Indonesia has several obstacles. These obstacles can be seen after researchers conducted field research on Judges and Prosecutors in Court jurisdictions who had handled money laundering cases with a nominal loss of 900 billion in Provinces that had high and medium risk of money laundering (in the vulnerable 2017 - 2019). To optimize criminal law enforcement, including the application of reversal burden of proof in the money laundering criminal justice system, it can be described based on the following variables: Legal Enforcement Knowledge Capacity; Ability to Actualize Norms; and Adequate Law Enforcement Instruments